Pengaruh Stres Kerja Pada Masa Pandemi Covid-19 Terhadap Kinerja Pekerja Instalasi Gawat Darurat (IGD) RS. Pusat Pertamina Di Jakarta - Ujang Supriadi; Zubair Azra; Fuad Gagarin (GEMILANG: Jurnal Manajemen dan Akuntansi, 2022)
This study describes two variables, namely job stress and worker performance. The purpose of this study was to analyze the relationship between work stress and the performance of hospital emergency room workers. Pertamina Headquarters in Jakarta. The work stress variable was tested using SRQ 20. While the worker performance variable was tested using 2 dimensions from the journal Emin Kahya. The research method used is quantitative research, conducted by distributing questionnaires to 30 emergency room workers at the hospital. Pertamina Center in Jakarta However, 24 questionnaires were collected again. Analysis of the data used is Spearman correlation. The results showed that the relationship between work stress and worker performance during the COVID-19 pandemic did not affect the performance of hospital emergency workers. Pertamina Center